E-103 Short-term in-hospital outcomes of thrombolysis for acute ischemic stroke patients with non-primary brain tumors and congestive heart failure. (22nd July 2019) - Tong, K; Colburn, T; Brauer, P
Abstract : Background: Intravenous thrombolysis remains an underutilized treatment for acute ischemic stroke (AIS) due to several relative and absolute contraindications. Previous studies have found similar outcomes after thrombolysis between AIS patients with benign brain tumors and AIS patients without. This study aims to investigate short-term outcomes of thrombolytic treatment for the greater majority of AIS patients who have no history of primary brain tumors, particularly those with congestive heart failure (CHF). Methods: This retrospective cohort study utilized data from the 2012–2015Q3 Nationwide Inpatient Sample (NIS). ICD-9 codes identified adult patients (ages 18+) who suffered acute ischemic stroke and received intravenous thrombolysis, and then further isolated patients diagnosed with CHF. Data for patients who were missing important clinical identifiers (age, gender, race, mortality), did not receive IV thrombolysis, and had primary brain tumors (benign or malignant) were excluded. Data analyses assessed hospital mortality rate, length of stay (LOS), inpatient charges, and average age of admission. Results: Of the 24, 692 encounters with AIS patients treated with thrombolysis and had no history of primary brain tumors, 4130 were diagnosed with CHF. Mean mortality rate was significantly increased (11.3% CHF vs. 11.8% no CHF, p<0.0001). Mean LOS was significantly longer (7.63 days CHF vs. 6.08 days no CHF, p<0.0001). Average total charges were significantly increased (96, 978.03 CHF vs. 83, 905.14 no CHF, p<0.0001). Average age at admission was significantly older (70.68 years CHF vs. 66.32 years no CHF, p<0.0001). Conclusion: This study aims to inform physicians to better manage AIS patients receiving IV thrombolysis with CHF and no history of primary brain tumors. These patients experience higher mortality rate, longer LOS, increased total hospital charges, and older age at admission than those without CHF. These findings suggest that placing clinical focus on the coexisting condition of CHF before administering IV thrombolysis for AIS may be critical for improving short-term in-hospital outcomes. Future research should aim to investigate different thrombolytic agents to determine the most optimal choice for patients with congestive heart failure. Disclosures: K. Tong: None. T. Colburn: None. P. Brauer: None.